PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN SITUASIONAL TERHADAP KEPUASAN KERJA PEGAWAI KANTOR CAMAT TIGA BINANGA KABUPATEN KARO - Selamat Siregar (Universitas Methodist Indonesia, 2022)
The leader's actions in providing directions and instructions will have a major impact on employee satisfaction. One option that can be taken in an effort to solve complex problems in an organization is to apply a transformational and situational leadership style approach. The purpose of this study is the influence of transformational and situational leadership on job satisfaction of employees of the Tiga Binanga District Office, Karo Regency. The sampling technique used by the researcher was saturated sampling, therefore the sample in this study was the entire population of employees in the Tigabinanga District Office, Karo Regency, totaling 33 people. The results of this study are that transformational leadership has a significant effect on employee job satisfaction in the Tigabinanga District Office, Karo Regency. Situational leadership has a significant effect on employee satisfaction at the Tigabinanga District Office, Karo Regency. Taken together, the leadership and situational transformation variables have a significant effect on employee job satisfaction in the Tigabinanga District Office, Karo Regency. The magnitude of the influence of transformational leadership and situational leadership on job satisfaction is 55.1%, the remaining 44.9% is explained by variables or other factors not discussed in this study.